Effect of different combinations of plant growth regulators and assessment of clonal fidelity among in vitro raised micro-shoots of pomegranate (Punica granatum L.) cv. Bhagwa - Pal, Devendra; Kumar, Mukesh; Yadav, Manoj Kumar; Chauhan, Chetan; Rani, Varsha; Pal, Anuj; Pandey, Vibhu (Plant Science Today, 2024)
The role of sodium nitroprusside (SNP) in plant development and growth is varied. However, there is currently no reported use of SNP in single or combined treatments for in vitro propagation of pomegranates. This study elaborates the role of SNP combined with different plant growth regulators (PGRs) like kinetin (Kn) and indole acetic acid (IAA) as supplementary in Murashige and Skoog (MS) media for in vitro propagation of pomegranate cv. Bhagwa using nodal segments as explants. The results revealed that treatment T9 (1.5 mg/L SNP + 1.5 mg/L Kn) resulted in the earliest shoot induction (25.03 days), the highest shoot proliferation (86.67 %) and the maximum shoot length (3.10 cm). However, treatment T8 (1.5 mg/L SNP + 1.0 mg/L Kn) produced the highest number of shoots/explant (2.60). In regards to in vitro rooting, the treatment fortified with T14 (2.0 mg/L IAA + 0.1 mg/L SNP) yielded the highest rooting frequency (100 %) with the maximum number of roots (4.77), while the treatment T15 (2.0 mg/L IAA + 0.2 mg/L SNP) exhibited earlier root initiation (13.17 days). The clonal fidelity analysis using ISSR markers revealed that the micro-propagated shoots were genetically uniform, with 88.89 % showing uniformity and a low level of somaclonal variation at 11.11 %.